LAM Genes Contribute to Environmental Stress Tolerance but Sensibilize Yeast Cells to Azoles - Sokolov, Svyatoslav S.; Vorobeva, Margarita A.; Smirnova, Alexandra I.; Smirnova, Ekaterina A.; Trushina, Nataliya I.; Galkina, Kseniia V.; Severin, Fedor F.; Knorre, Dmitry A. (Frontiers in Microbiology, 2020)
Lam proteins transport sterols between the membranes of different cellular compartments. In Saccharomyces cerevisiae, the LAM gene family consists of three pairs of paralogues. Because the function of paralogous genes can be redundant, the phenotypes of only a small number of LAM gene deletions have been reported; thus, the role of these genes in yeast physiology is still unclear. Here, we surveyed the phenotypes of double and quadruple deletants of paralogous LAM2(YSP2)/LAM4 and LAM1(YSP1)/LAM3(SIP3) genes that encode proteins localised in the junctions of the plasma membrane and endoplasmic reticulum. The quadruple deletant showed increased sterol content and a strong decrease in ethanol, heat shock and high osmolarity resistance. Surprisingly, the quadruple deletant and LAM2/LAM4 double deletion strain showed increased tolerance to the azole antifungals clotrimazole and miconazole. This effect was not associated with an increased rate of ABC-transporter substrate efflux. Possibly, increased sterol pool in the LAM deletion strains postpones the effect of azoles on cell growth. Alternatively, LAM deletions might alleviate the toxic effect of sterols as Lam proteins can transport toxic sterol biosynthesis intermediates into membrane compartments that are sensitive to these compounds. Our findings reveal novel biological roles of LAMgenes in stress tolerance and suggest that mutations in these genes may confer upregulation of a mechanism that provides resistance to azole antifungals in pathogenic fungi.